Cardiovascular risk in pediatric nonalcoholic fatty liver disease: recent advances. (August 2015) - Baskar, Shankar; Jhaveri, Simone; Alkhouri, Naim
Nonalcoholic fatty liver disease (NAFLD) is the most common form of pediatric chronic liver disease in developed countries. NAFLD has risen to epidemic proportions paralleling that of childhood obesity. It is becoming increasingly evident that NAFLD is strongly linked with cardiovascular disease (CVD), which is the leading cause of mortality in the adult NAFLD population. It is very important for physicians caring for children being cognizant of the potential role of childhood NAFLD as an independent risk factor for CVD. Childhood is a time period where subclinical CVD can be detected, giving us the potential ability to halt or reverse the disease process. In this review, we discuss recent evidence linking childhood NAFLD to CVD and potential pathogenic links.